A stereoselective hydride transfer reaction with contributions from attractive dispersion force control. Issue 32 (24th March 2022) - Braddock, D. Christopher; Limpaitoon, Natnicha; Oliwa, Krzysztof; O'Reilly, Daniel; Rzepa, Henry S.; White, Andrew J. P.
Abstract : The experimentally determined stereochemical outcome of an unprecedented hydride transfer from a lithium alkoxide to an aldehyde is reported, as deconvoluted by the combined use of a single enantiomer alkoxide in conjunction with a deuterium label. Abstract : The experimentally determined stereochemical outcome of an unprecedented hydride transfer from a lithium alkoxide to an aldehyde is reported, as deconvoluted by the combined use of a single enantiomer alkoxide in conjunction with a deuterium label. The stereoselective outcome is consistent with a computationally predicted transition state model stabilised by contributions from attractive dispersion forces.